Anemia in Indigenous youth from an Amazonian community in Brazil exposed to mercury during a major environmental impact from gold mining activities - Angélica dos Santos Vianna; Aline de Souza Espindola Santos; Carmen Ildes Rodrigues Fróes Asmus; Iracina Maura de Jesus; Ronir Raggio Luiz; Volney de Magalhães Câmara (Cadernos de Saúde Coletiva)
Abstract Background Mercury (Hg) is a highly toxic substance that can affect various body systems, including the hematopoietic system. However, information on its impact on humans remains limited. This study evaluates the potential association between anemia and Hg exposure among Indigenous children and youth from an Amazonian community in Brazil. Objective To evaluate the association between anemia in indigenous children and adolescents and exposure Hg. Method Secondary data analysis from a cross-sectional study comprising 95 Indigenous children and youth from an Amazonian community in Brazil. Descriptive analysis was conducted on the population’s characteristics, eating habits, pathologies, and Hg concentrations in hair samples. Logistic regression was applied to assess the association between anemia and Hg exposure, adjusted for potential confounders. Results Of the 95 individuals evaluated, 48.4% presented anemia, while median hair Hg levels were notably high (14.6 µg/g; IQR: 12.3–19.2 µg/g), even at the lowest recorded concentration (6.8 µg/g). A significant association was identified between anemia and Brazil nut consumption (OR=0.27; 95% CI=0.04-0.98), and between anemia and hair Hg levels ≥10 µg/g (OR=1.22; 95% CI=0.99-1.97). Conclusion The prevalence of anemia in this population is severe, and elevated hair Hg levels were observed. These findings suggest a preliminary link between high Hg exposure and the developed anemia. Considering the complexity of anemia in this population and its potential long-term health impacts, further research is necessary to elucidate the role of Hg exposure in this condition.